(untitled) (Fiep Bulletin - online, 2012)
This study investigated the alterations in physical fitness during menstrual cycle in women practicing resistance exercise. The sample included ten women from Gloss gym, exercising to 6 months, age 29.4 years (± 4.6), height 1.61mt (± 0.08) and cycles of 28 days. Were evaluated the three phases of the menstrual cycle, starting by Follicular (FO) (1° to 4º day), after Ovulatory (OP) (14° day) and Luteal Phases (LP) (26° to 28° day). The following measurements were performed: total body mass, body fat (%), lean mass (%), flexibility, VO2máx. and perceived exertion (EPE) testing in the 10RM leg press 45° and pulley machines. The comparison of results at different times of the cycle was performed by one way ANOVA with repeated measures and significant level of p <0.05.Total body mass presented higher in the LP (70.32kg ± 12.39) compared to FO and OP (69.44kg ± 12.48 and 69.07kg ± 12.35, respectively, p<0.0001). EPE score in phase Ovulatory (2.40 ± 0.96) was higher compared to FO (1.20 ± 0.63) in the exercise leg press 45° (p<0.05). VO2máx. was significantly lower (p<0.0001) in the LP (34.80 ml/kg/min-1) compared to FO and OP (36.02 ml/kg/min-1 ± 2.7 e 36.85 ml/kg/min-1 ± 2.5, respectively). Body fat differed (p<0.0001) among all phases of the menstrual cycle (FO=37.20 % ± 5.6; OV=36.72 % ± 5.8 and LU 34.80% ± 2.5) and the lean mass was only significantly difference between OP and LP phases (26.90% ± 2.2 e 26.36% ± 2.1, respectively, p<0.05). OP phase the flexibility was higher compared to LP (29.40 cm ± 5.5 e 28.60 cm ± 5.6, respectively, p<0.05).Our findings show that physical fitness is influenced by different cycle menstrual phases.